PENGEMBANGAN MODUL IPS MATERI INTERAKSI MANUSIA DENGAN LINGKUNGAN BERBASIS LITERACRAFT UNTUK MENINGKATKAN GREEN BEHAVIOUR SISWA KELAS V SEKOLAH DASAR - Fadia Zulfiana, - (2022)
This research is motivated by the low behavior of maintaining and maintaining or green behavior of students because there is no module that develops green behavior material. Based on this, this study aims to develop a social science module on human interaction with the environment based on literacy to improve green behavior for fifth grade elementary school students. The research method used in this research is the Design and Development (D&D) method developed by Branch, through five stages, namely analysis, design, development, implementation, evaluation, which can be abbreviated as ADDIE. The development of the module design was carried out by researchers systematically arranged including module cover components, student identity, introduction, table of contents, mapping of basic competencies, learning objectives, instructions for using modules, module content or material, practice questions, student worksheets, reflection journals, success displays. complete the module, and answer keys. The results of the expert validation assessment carried out to material experts, media experts, and module experts were in the form of a questionnaire with a score presentation of 90% from material experts, from media experts to 100%, and from linguists to 84.4%. With the results of the average percentage of scores from all experts of 91.4% in the very good category. The social studies module was also tested on fifth grade elementary school students through pre-test and post-test. The test results of this IPS module showed an increase in the results of the pre-test and post-test from an average of 51.6 to 88.4. In addition, the researchers conducted the Ngain test from Ngain from the pretest and posttest that had been done by students, the average calculation results showed a value of 76.67% with an effective category. With this, it can be said that the development of the social studies module on human interaction with the literacy-based environment is feasible and can improve the green behavior of 5th grade elementary school students.